THE EFFECT OF LIQUID ORGANIC FERTILIZER (LOF) DERIVED FROM LEUCAENA LEAVES (Leucaena leucocephala) AND PINEAPPLE PEELS (Ananas comosus L.) ON PAK CHOI (Brassica rapa subsp. chinensis) GROWTH - Yosilia, Rani; Joevira, Ayu Ela; Winandari, Ovi Prasetya (Universitas Lampung, 2025)
Rapid population growth and increasing demand for high-quality food drive the need for innovation in the agricultural sector. The main challenge faced is how to enhance production efficiency and the quality of agricultural yields sustainably. Pak choi, one of the fast-growing crops in Indonesia, requires special attention through various innovations to support its optimal growth. One of the key factors in pak choi growth is fertilization. However, the continuous use of synthetic fertilizers can damage soil fertility. As a sustainable alternative, Liquid Organic Fertilizer (LOF) has been developed from recycled green waste, specifically Leucaena leaves and pineapple peels. This study aims to evaluate the effects of LOF application derived from these organic waste materials on pak choi growth. This research was conducted in Sugih Waras Village, Belitang Mulya District, East OKU Regency. The research method used was a Completely Randomized Design (CRD) with 5 treatments and 3 replications. Data were analyzed using ANOVA and further tested with HSD at a 5% significance level. The results showed that the application of LOF had the best effect in the treatment was 45 ml LOF/polybag, with plant height reaching 21 cm, 23 leaves, root length of 15 cm, fresh plant weight of 116 grams, and dry plant weight of 12.1 grams.